TINGKAT KERUSAKAN TEGAKAN HUTAN AKIBAT OPERASI PENEBANGAN PADA DUA HAK PENGUSAHAAN HUTAN DI KALIMANTAN BARAT - Jurnalis Thaib (Jurnal Penelitian Hasil Hutan, 1989)
Minimum   level   of  stand  damages  is one  of  the  obyectives   of  the  tropical  rain  forest  harvesting  practices  in which the  Indonesian   Selective   Cutting  system   is applied.  In order  to  meet  that  obyective,   various manuals  should   be prepared based on sound  quantitative  data.Observation    on stand  damages  due  to felling  operations  has been  carried out  in Suka Jaya  Makmur  Enterprise  (SJM) and  Kawedar  Mukti   Timber   Enterprise   (KMT),   both   located   in  West Kalimantan.   The  stand  damages  caused  by  felling one  tree  vary  from   3  to  8  trees with   an average  of  6 trees  in SJM,  and  from  2  to  7  trees  with   an average of  4  trees  in KMT.  The  relationships    between   stand  damage  (Y)  and  stand  density   (X)  are: Y = -4,69   + 0,08   X for SJM and  Y = -6,83+ 0,08 X for KMT.The  results  of  the  study  showed   that  the  major  causes of  the  variation  of  stand  damages  are  improper  direction  of tree felling,   and  less control  from  supervisors/managers.